Recognition and treatment of endometriosis involving the sacral nerve roots. Issue 1 (January 2016) - Lemos, Nucelio; D'Amico, Nicolau; Marques, Renato; Kamergorodsky, Gil; Schor, Eduardo; Girão, Manoel
Abstract Introduction and hypothesis Endometriosis involving the sacral plexus is still poorly understood or neglected by many surgeons. Looking at that scenario, we have designed this educational video to explain and describe the symptoms suggestive of endometriotic involvement of the sacral plexus in addition to the technique for the laparoscopic treatment of this condition. Methods Retrospective analysis of 13 consecutive cases of endometriotic entrapment of nerves of the lumbosacral plexus. Results Pairedt test revealed a statistically significant (p  < 0.0000001) reduction in pain VAS score, from preoperative average 9.1 (±1.98) to postoperative 1.46 (±1.66). Twelve out of 13 patients (92.3 %) experienced a reduction of 50 % or more in VAS score and 6 (46.15 %) became completely pain-free. Conclusion The signs suggestive of intrapelvic nerve involvement include perineal pain or pain irradiating to the lower limbs, lower urinary tract symptoms, tenesmus or dyschezia associated with gluteal pain. Whenever deeply infiltrating lesions are present, the patient must be asked about those symptoms and specific MRI sequences for the sacral plexus must be taken, so that the equipment and team can be arranged and proper treatment performed.